Apprenticeship : dual vocational education and training in Austria ; modern training with a future - Achleitner, Dagmar [Herausgeber]; Wallner, Josef [Herausgeber]; Schönherr, Anna [Herausgeber] (Federal Ministry of Science, Research and Economy, 2014)
This brochure provides a comprehensive overview of apprenticeship training in Austria. Topics of further consideration are - amongst others - the different places of learning, financing of apprenticeship training, new regulation of occupations, modularisation, apprenticeship and matura, inclusive vocational training, and apprenticeship training in a European context. The annex contains an excerpt from a training regulation (apprenticeship "Installations and building technology"), a list of institutions involved in apprenticeship training, and a list of apprenticeship trades with the respective training periods. (BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; I 2.2.1 Westeuropa; Berufsbildungssystem; Duales System; Betriebliche Berufsausbildung; Österreich